AKIBAT HUKUM ITSBAT NIKAH TERHADAP PERKAWINAN TIDAK DICATAT BERDASARKAN KOMPILASI HUKUM ISLAM PADA PENGADILAN AGAMA CIBINONG KELAS 1B - Dea Pitri Maelani; Ani Yumarni; Innayatullah Abd. Hasyim (JURNAL HUKUM DE'RECHTSSTAAT, 2017)
In the district. Bogor many people who perform marriages were not registered. It is caused by several factors, one of which is the lack of knowledge of the importance of marriage registration. Then the problems that will be studied are: 1) how the foundation philosophy contained in the petition Ithbat Marriage under Law No. 3 of 2006 on the Religious Courts Cibinong Class 1B, 2) how the judge in the consideration granted Ithbat marriage on marriage were not recorded after the enactment of Law No. 1 Year 1974 on Marriage. The purpose of research is 1) to assess and determine the foundation philosophy contained in the authority of Judge cremate Ithbat marriage petition under the Act No. 3 of 2006 on the Religious Courts Religious Courts Cibinong Class 1B, 2) to study and know the judge in the consideration granted Ithbat marriage on marriage were not recorded conducted after the enactment of Law No. 1 Year 1974 on Marriage. The method used is the method of sociological juridical approach to data collection techniques of observation and interviews.   Registration of marriages arranged in Paasal 2 paragraph (2) of Law No. 1 Year 1974 on Marriage. In absolute competence of the Religious Court, namely Article 49 of Law No. 3 In 2006 one of them is "a statement about the validity of marriages that occurred before the Act No. 1 Year 1974 on Marriage and executed according to other regulations. With reinforced with Compilation of Islamic Law, and consideration mashlahah mursalah Court judge granted the petition Ithbat Religion remains Nikah marriage that occurred after the enactment of Law No. 1 Year 1974 on Marriage.